2017
DOI: 10.2147/dddt.s123939
|View full text |Cite
|
Sign up to set email alerts
|

Development of erythropoietin receptor-targeted drug delivery system against breast cancer using tamoxifen-loaded nanostructured lipid carriers

Abstract: Tamoxifen (TAM) has been used in the treatment of breast cancers and is supplemented with erythropoietin (EPO) to alleviate the cancer-related anemia. The purported deleterious effects caused by the use of EPO with chemotherapeutic agents in the treatment of cancer-related anemia vary across studies and remain controversial. The use of nanoparticles as a drug delivery system has the potential to improve the specificity of anticancer drugs. In this study, we simultaneously incorporated two pharmacological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
(40 reference statements)
1
8
1
Order By: Relevance
“…25 Recently, EPO-conjugated TAM-loaded lipid nanoparticles enhanced the in vitro cytotoxicity of TAM to MCF-7 cells and showed that EPOR expressed on cancer cells is a potential receptor for drug-targeted therapy. 26 Although EPOR has been detected with specific A82 antibody in A2780 cells (Fig. 1B), neither the effect of 10 IU/ ml nor the effect of 100 IU/ml of EPO on the proliferation of these cells was observed.…”
Section: Resultsmentioning
confidence: 84%
“…25 Recently, EPO-conjugated TAM-loaded lipid nanoparticles enhanced the in vitro cytotoxicity of TAM to MCF-7 cells and showed that EPOR expressed on cancer cells is a potential receptor for drug-targeted therapy. 26 Although EPOR has been detected with specific A82 antibody in A2780 cells (Fig. 1B), neither the effect of 10 IU/ ml nor the effect of 100 IU/ml of EPO on the proliferation of these cells was observed.…”
Section: Resultsmentioning
confidence: 84%
“…Structurally, EPO-TAMNLC comprises of loaded TAM within the core and a coating of EPO on the surface of the nanoparticles. Since EpoR are highly expressed in breast cancers [12, 29], EPO coating on EPO-TAMNLC surfaces serve as the ligand in the binding of the nanoparticles to EpoR on the breast cancer cells [15]. EPO does not compromise the efficaciousness of breast cancer chemotherapeutics [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…EPO does not compromise the efficaciousness of breast cancer chemotherapeutics [30, 31]. In fact, in an early study, we showed that EPO-TAMNLC and TAMNLC had greater antiproliferative effect on MCF-7 cells than TAM [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7): higher encapsulation efficiency, better control of drug release and lower drug expulsion during product storageSÁNCHEZ-LÓPEZ et al, 2017). Thus, these nanocarriers have been used in the preparation of low water solubility drugs to increase the efficacy and reduce toxicity(BEH et al, 2017) Figure 1.6. Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) structures and NLC advantages.…”
mentioning
confidence: 99%